2009
DOI: 10.1111/j.1755-053x.2009.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Ratings and Firm Performance

Abstract: "We examine the corporate governance ratings provided by three premier US rating agencies and find that summary scores are generally poor predictors of primary and secondary measures of future firm performance. However, some component sub-ratings that focus on the eight key dimensions of dynamic governance structures provide more positive and reliable evidence of their information content in predicting the multiple dimensions of firm performance. These results reflect the recent observations by academic resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 28 publications
3
43
0
3
Order By: Relevance
“…However, there is little empirical research on the role of corporate governance quality measured by those governance ratings in assessing fund performance (Chou et al 2007;Ertugrul and Hegde 2009;Wellman and Zhou 2007). However, there is little empirical research on the role of corporate governance quality measured by those governance ratings in assessing fund performance (Chou et al 2007;Ertugrul and Hegde 2009;Wellman and Zhou 2007).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…However, there is little empirical research on the role of corporate governance quality measured by those governance ratings in assessing fund performance (Chou et al 2007;Ertugrul and Hegde 2009;Wellman and Zhou 2007). However, there is little empirical research on the role of corporate governance quality measured by those governance ratings in assessing fund performance (Chou et al 2007;Ertugrul and Hegde 2009;Wellman and Zhou 2007).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Based on the Corporate Governance Quotient index (CGQ) reported by the ISS, Epps and Cereola (2008) identified the lack of a significant relationship between the corporate governance rating and operational performance represented by the rate of return on assets and the return on equity ratio. Ertugrul and Hegde (2009) have established that the ratings developed by TCL (The Corporate Library) and the ISS are negatively associated with future operating performance, while the GMI ratings (Governance Metrics International) are positively correlated. Daines et al (2010), using the CGQ (RiskMetrics/ISS), GMI, and TCL indices, have identified a lack of predictive skills regarding future performance.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…On the related f eld of corporate governance,Ertugrul and Hegde (2009) state that overall ratings have poor predictive power, while eight key sub-components have signif cant information content.…”
mentioning
confidence: 99%